RETRACTED ARTICLE: Comprehensive investigations of mixed convection of Fe–ethylene-glycol nanofluid inside an enclosure with different obstacles using lattice Boltzmann method - Chenqi Fu; Amin Rahmani; Wanich Suksatan; S. M. Alizadeh; Majid Zarringhalam; Supat Chupradit; Davood Toghraie (Scientific Reports)
Abstract In the present paper, nanofluid mixed convection is investigated in a square cavity with an adiabatic obstacle by using the Lattice Boltzmann method (LBM). This enclosure contains Fe–ethylene-glycol nanofluid and three constant temperature thermal sources at the left wall and bottom of the enclosure through a lateral wall. The fluid is incompressible, laminar, and Newtonian. The obtained results are presented in the constant Ra = 104 and a Pr = 0.71 for different Ri = 0.1, 1, and 10. The effects of the slope of the enclosure, volume fraction of nanoparticles $$\left( φ \right)$$ φ , the location of adiabatic obstacles, and nanoparticle diameter in the fluid are investigated on the value of heat transfer. A change in the attack angle of the enclosure leads to changes in the movement distance for fluid between hot and cold sources and passing fluid through case E, which affects the flow pattern strongly. In each attack angle, on colliding with an obstacle, the fluid heat transfers between two sources, which leads to uniform heat transfer in the enclosure. By increasing the velocity of the lid, the Richardson number decreases leading to improvement of the convective heat transfer coefficient and Nusselt number enhancement. The results so obtained reveal that by augmenting $$φ$$ φ value the effect of Richardson number reduction can augment Nusselt number and the amount of absorbed heat from the hot surface. Consequently, in each state where a better flow mixture and lower depreciation of fluid velocity components, due to the penetration of lid movement and buoyancy force, occurs higher heat transfer rate is accomplished. Furthermore, it is shown that when Ri = 0.1, the effect of cavity angle is more important but when Ri = 10, the effect of the position of obstacle is more visible.